Gravity, massive particles, photons and Shapiro delay - Wilhelm K.; Dwivedi B.N. (My University, 2025)
An impact model of gravity designed to emulate Newton's law of gravitation is applied to particles with relative motions at slow and relativistic speeds. Based on this model, a gravitational interaction mode is then conceived between photons and massive particles. This implies a deflection perpendicular to the propagation direction of a photon twice as large as expected from the mass-energy relation of photons-in accordance with observations and the General Theory of Relativity. The longitudinal interaction is compatible with the energy and momentum conservation principles applied to massless entities, and the results are consistent with the observed Shapiro delay. © 2012 Springer Science+Business Media B.V.